Race, revolution, and the struggle for human rights in Zanzibar the memoirs of Ali Sultan Issa and Seif Sharif Hamad - Burgess, G. Thomas (Athens Ohio University Press, 2013)
Zanzibar has had the most turbulent postcolonial history of any part of the United Republic of Tanzania, yet few sources have emerged that explain the reasons why. The current political impasse in the islands is a contest primarily over the question of whether to accept and sustain the Zanzibari Revolution of 1964. Defenders of the revolution speak the language of African nationalism and aspire to unify the majority of Zanzibar through the politics of race. Their opponents claim, instead, that the revolution undermined the islands? cosmopolitan cultural heritage and espouse the language of human rights.
Includes bibliographical references (p. 313-328) and index.
Keywords: Issa, Ali Sultan